Modification of Electric Properties of Lithium Niobate Crystals by Ion Bombardment - Pichugin V. F. Vladimir Fyodorovich; Bulycheva A. A.; Riabzeva M. A.; Ill Won Kim (Fundamentals of modification processes, 2004)
Title from the title-page.